Nutzung von Medizin-Apps und Online-Plattformen unter deutschen Rheumatologen - Knitza, Johannes; Vossen, D.; Geffken, I.; Krusche, M.; Meyer, M.; Sewerin, P.; Kleyer, Arnd; Hueber, Axel (Zeitschrift für Rheumatologie, 2019)
Background: Apps and online platforms play an ever increasing role in the daily work routine of physicians. The aim of this study was to investigate which medical apps and online platforms are used by German rheumatologists for certain tasks and to identify usage trends. Methods: Data were collected via a SurveyMonkey survey conducted by members of rheumadocs (Young German Rheumatology Association) at the 2016 and 2018 German Society for Rheumatology (DGRh) conferences. Results: In 2016 and 2018 the survey was completed by 75 and 84 assistant and specialist rheumatologists, respectively. In 2016, 37% of rheumatologists were using medical apps in routine care which changed to 49% in 2018. In 2016, 47% compared to 68% in 2018, planned to integrate medical apps into routine care. In total, 20 different medical apps were recommended for colleagues to use; however only 2 of these apps were specific for rheumatology. In contrast to 52 app recommendations for colleagues, only 8 app recommendations for patients were recorded. Most recommendations to physicians received the app “Arznei aktuell” (21%). “Embryotox” was the app, most recommended to patients (38%). In 2016 the online database PubMed was most popular and 97% of participants were familiar with it. Use of other online platforms showed great age dependency in 2016: Amboss (a digital learning platform) was used by 31% of the age group 21–30 years and was not used at all by the age group 51–60 years. Discussion: Use of medical apps and planned integration of medical apps into routine care is increasing among German rheumatologists. On the other hand, recommendable rheumatological apps for rheumatologists and especially for patients are currently largely unknown to rheumatologists.
CRIS-Team Scopus Importer:2019-11-12
Keywords: eHealth; Medical apps; mHealth; Rheumatology; Telemedicine